Design and National Dissemination of the StrongWomen Community Strength Training Program - Rebecca A. Seguin, MS; Christina D. Economos, PhD; Raymond Hyatt, PhD; Ruth Palombo, PhD; Peter N.T. Reed, MPH; Miriam E. Nelson, PhD (Preventing Chronic Disease, 2008)
BackgroundPhysical activity is essential for maintaining health and function with age, especially among women. Strength training exercises combat weakness and frailty and mitigate the development of chronic disease. Community-based programs offer accessible opportunities for strength training.Program DesignThe StrongWomen Program is an evidence-informed, community-based strength training program developed and disseminated to enable women aged 40 or older to maintain their strength, function, and independence. The StrongWomen Workshop and StrongWomen Tool Kit are the training and implementation tools for the StrongWomen Program. Program leaders are trained at the StrongWomen Workshop. They receive the StrongWomen Tool Kit and subsequent support to implement the program in their communities.DisseminationProgram dissemination began in May 2003 with a three-part approach: recruiting leaders and forming key partnerships, soliciting participant interest and supporting implementation, and promoting growth and sustainability.AssessmentWe conducted site visits during the first year to assess curriculum adherence. We conducted a telephone survey to collect data on program leaders, participants, locations, and logistics. We used a database to track workshop locations and program leaders. As of July 2006, 881 leaders in 43 states were trained; leaders from 35 states had implemented programs.ConclusionEvidence-informed strength training programs can be successful when dissemination occurs at the community level using trained leaders. This research demonstrates that hands-on training, a written manual, partnerships with key organizations, and leader support contributed to the successful dissemination of the StrongWomen Program. Results presented provide a model that may aid the dissemination of other community-based exercise programs.